Modeling acousto-optic sensing of high-intensity focused ultrasound lesion formation. - Adams, M; Giraud, D; Cleveland, R; Roy, R (2012)
Real-time acousto-optic (AO) sensing has been shown to non-invasively detect changes in tissue optical properties, a direct indicator of thermal damage, during high-intensity focused ultrasound (HIFU) therapy. In this work, a comprehensive model is developed to describe the AO sensing of lesion formation during HIFU therapy. The angular spectrum method is used to model ultrasound propagation, and the temperature field due to the absorption of ultrasound is modeled using a finite-difference time-domain (FDTD) solution to the Pennes bioheat equation. Thermal damage dependent optical properties are calculated based on a probabilistic and calibrated thermal dose model. To simulate light propagation inside of insonified and optically heterogeneous tissue, an open-source graphics processing unit (GPU) accelerated Monte Carlo algorithm is used. The Monte Carlo algorithm is modified to account for light-sound interactions, using input from the angular spectrum method, and to account for AO signal detection. Results will show how wavelength and illumination/detection configurations affect the detectability of HIFU lesions using AO sensing.